Sabrina P. Ramet, Alternatives to Democracy in Twentieth-Century Europe: Collectivist Visions of Modernity (Budapest; New York: Central European University Press, 2019), xiv + 477 str. (Časopis za suvremenu povijest, 2020)
Prikaz knjige